Resilience of Firms to Economic and Climate Shocks Initial Insights from Philippine SMEs - Jamil Paolo Fransisco; Ailyn Lau; Ronald U. Mendoza (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
Households and businesses need to cope and thrive in an increasingly shock-prone world. Development and poverty reduction strategies need to take careful account of efforts to promote not just more resilient households and communities; but also more resilient firms on which many jobs and livelihoods depend on. Public sector and donor support for disaster- and crisis-hit communities is critical; but it is only when firms get back up that the community is able to recover fully. Once firms are able to start operating again, then workers are able to return to their jobs and the domestic economy is able to return to normal. Stronger resilience over time is also expected to reflect more robust economic competitiveness and yield more robust investments. The goal of this study is to assess the resilience of the Philippines’ small and medium scale enterprises (SMEs) during economic and environmental shocks. The main focus here is on firms’ resilience during the global financial crisis and economic slowdown in 2008-2010 and the major floods that hit the country in 2009 and 2011. These climate-related shocks affected cities such as Marikina, Iligan, and Cagayan de Oro. SMEs in these cities will be the main focus of this study.